2012
DOI: 10.1002/dneu.22057
|View full text |Cite
|
Sign up to set email alerts
|

β2 and γ3 laminins are critical cortical basement membrane components: Ablation of Lamb2 and Lamc3 genes disrupts cortical lamination and produces dysplasia

Abstract: Cortical development is dependent on the timely production and migration of neurons from neurogenic sites to their mature positions. Mutations in several receptors for extracellular matrix (ECM) molecules and their downstream signaling cascades produce dysplasia in brain. Although mutation of a critical binding site in the gene that encodes the ECM molecule laminin γ1 (Lamc1) disrupts cortical lamination, the ECM ligand(s) for many ECM receptors have not been demonstrated directly in the cortex. Several isofor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 57 publications
(87 reference statements)
4
57
0
Order By: Relevance
“…Iba1-expressing microglia were present in heterotopia but microglial morphology did not indicate an activated phenotype (data not shown). In order to confirm these results, we examined primary histological material in our laboratory of brains of laminin β2/γ3 double-KO mice which develop numerous MLH throughout most of the neocortex [14]. Similar to our observations in C57BL/6J mice, we found that Iba1-expressing microglia were present in heterotopia in laminin β2/γ3 double-KO mice (data not shown).…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Iba1-expressing microglia were present in heterotopia but microglial morphology did not indicate an activated phenotype (data not shown). In order to confirm these results, we examined primary histological material in our laboratory of brains of laminin β2/γ3 double-KO mice which develop numerous MLH throughout most of the neocortex [14]. Similar to our observations in C57BL/6J mice, we found that Iba1-expressing microglia were present in heterotopia in laminin β2/γ3 double-KO mice (data not shown).…”
Section: Resultssupporting
confidence: 64%
“…MLH have also been observed in several knockout (KO) mice [14,15,16,17,18,19,20,21,22,23]. MLH in mice are indistinguishable from heterotopia observed in humans.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Experimental disruption of ECM, ECM receptors and mechanosignaling proteins in neural cells can dramatically affect early brain development. For example, mutation of the subunits laminin β2 and laminin γ3 causes laminar disruption of the cortex (Radner et al, 2013), and mice lacking FAK in the dorsal forebrain also exhibit cortical lamination defects, neuronal dysplasia and abnormal synapse formation (Beggs et al, 2003;Rico et al, 2004). Although these studies represent manipulations of proteins involved in mechanosignaling, the resulting effects on cell adhesion could also directly contribute to the observed phenotypes.…”
Section: Mechanical Forces Guide Brain Developmentmentioning
confidence: 99%
“…Goat anti-rabbit 488 and 568, goat anti-rat 488 and 568, donkey anti-rabbit 488 and 594, and donkey anti-rat 488 and 594 (Life Technologies, Grand Island, NY, USA) secondary antibodies were used. The specificity of the laminin antibodies has been published previously: anti-β2 (Pinzón-Duarte et al, 2010;Radner et al, 2013) and anti-γ3 antibodies (Li et al, 2012). The following laminins were used: EHS-laminin (Life Technologies), recombinant laminin-521 (BioLamina, Stockholm, Sweden) and laminin 5 (a gift from Dr Manuel Koch, Universität zu Köln, Germany).…”
Section: Reagentsmentioning
confidence: 99%